The talent paradox: Disenchantment, disengagement, and damage through sport - Massey, W. V.; Whitley, M. A. (Sociology of Sport Journal, 2020)
Previous researchers have demonstrated that sport participation can be a place of purpose, a place of celebrated deviance, and/or a value-neutral endeavor for children who have experienced developmental trauma. While previous research has focused primarily on sport as a positive influence, the purpose of this paper is to examine where disillusionment, disengagement, and damage occur through participation in sport. This study was guided by a constructionist epistemology, with the researchers aiming to understand how sport participation interacted with various system-level influences. Interviews were conducted with 41 former athletes, significant others, and community members. The results of this study explore how a sport system can contribute to disillusionment in sport, disengagement from sport, and damage done through sport.